Stopa procentowa i efektywność - Smoluk, Antoni (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Polygonal functions, which are observed in daily courses diagrams, are nothing more than projections of screw line whirling around the point of equilibrium. By this motion we are receiving two-dimensional surface of Stock Exchange states - a cone. The periodical motion results because of a constant changes of the equilibrium point. Crucial proposition of the paper can be reduced to the change of the two-dimensional classical picture into the three-dimensional natural space defined by time, price and volume of the stocks. Principle of stability. The whirpool motion is the essence of economy: in that way an economical system tends to the ideal state of equilibrium. Periodicity principle. Economical cycles are the consequence of Newton principle; the equilibrium of an economy appears in these cycles. Here are also given the two laws of finance. Law of the decreasing rates. An industrial development implies some decreasing the prices of the capital. In a long period of time the rates of interest are converging to zero. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 467-474